Recent Publications (Quarterly Journal of Economics, 1949)
Recent Publications Get access The Quarterly Journal of Economics, Volume 63, Issue 4, November 1949, Pages 584–585, https://doi.org/10.1093/qje/63.4.584 Published: 01 November 1949